Documentation for derivatives : annotated sample agreements and confirmations for swaps and other over-the-counter transactions - Gooch, Anthony C.; Klein, Linda B. (London [Eng.] : Euromoney Books, 2002)
Written by leading US financial lawyers, this guide has been fully revised and updated. Volume 2 includes a clause by clause examination of ISDA-based master agreements. This is a useful documentation tool for anyone working in or around the derivatives market.
Includes index.
Paged continuously.
Previous ed.: 1993.
oif 25/08/15
Loan
Keywords: Derivative securities -- Law and legislation; Swaps (Finance) -- Law and legislation; Swaps (Finance); Over-the-counter markets; Interest rate futures; Foreign exchange futures